Legal Protection Of Children From The Psychological Impact Of Broken Homes - Puspita, Putri; Khusnul Khotimah; Saiyidah Cahyani; Nur Baiti Islamiyah; Suniati; R.P.M Ganif Abimanyu; Hikmah (Fakultas Hukum Universitas Widya Mataram, 2025)
The phenomenon of broken home families is an increasingly prevalent social condition that has serious impacts on the psychological development of children. Children who grow up in incomplete family environments are at risk of experiencing emotional stress, behavioral disorders, and an overall decline in quality of life. This study aims to examine the forms of legal protection for children who suffer psychological impacts due to broken home families. The research method used is normative legal research, with a statutory and conceptual approach. Data sources were obtained through literature studies of legislation, legal doctrines, and relevant court decisions. The results of the study indicate that legal protection for children in Indonesia is regulated in various legal instruments, including Law Number 35 of 2014 concerning Child Protection, as well as provisions in the Civil Code and Law Number 1 of 1974 concerning Marriage. However, the implementation of this protection has not been fully effective, particularly in the aspect of psychological recovery for children. Therefore, it is necessary to strengthen the role of child protection institutions, increase legal awareness among parents, and integrate legal and psychological aspects in efforts to protect children holistically.